Sustainable Energy-Water-Environment Nexus in Deserts Proceeding of the First International Conference on Sustainable Energy-Water-Environment Nexus in Desert Climates - Heggy, Essam; Bermudez, Veronica; Vermeersch, Marc. (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book addresses challenges and opportunities in the Energy-Water-Environment (EWE) nexus, with a particular focus on research and technology development requirements in harsh desert climates. Its chapters include selected contributions presented during the 1st international conference on sustainable Energy-Water-Environment nexus in desert climates (ICSEWEN-19) held at the Qatar Environment and Energy Research Institute (QEERI) in Doha, Qatar in December 2019. This volume is comprised of three main chapters, each describing important case studies and progress on water, energy and environmental questions. A fourth chapter on policies and community outreach on these three areas is also included. This compilation aims to bridge the gap between research and industry to address the socioeconomic impacts of the nexus imbalance as perceived by scientists, industrial partners, and policymakers. The content of this book is of particular importance to graduate students, researchers and decision makers interested in understanding water, energy and environmental challenges in arid areas. Re searchers in environmental and civil engineering, chemistry, hydrology and environmental science can also find unique in-situ observations of the current nexus imbalance in deserts climate to validate their investigations. It is also an invaluable guide for industry professionals working in water, energy, environment and food sectors to understand the rapidly evolving landscape of the EWE nexus in arid areas. The analyses, observations and lessons-learned summarized herein are applicable to other arid areas outside North Africa and the Arabian Peninsula as well, such as central Australia, the southwest of the United States and deserts in central Asia.
Modelling the effect of the pumping variations' on the groundwater quality in the semi-arid Aquifers -- Assessment of Groundwater Aquifer Impact from Artificial Lagoons and the Re-use of Wastewater in Qatar -- Temporal groundwater level prediction using multivariate geostatistics: a case study from Sfax superficial aquifer (Tunisia) -- Integration of electromagnetic method and resistivity depth sounding in the evaluation of groundwater potentials of Araromi phases 1 and 2, Akungba-Akoko, southwestern Nigeria -- Contribution to the Study of Fluoride Ion Concentrations in Groundwater and its Impact on the Desert Areas of South-eastern Algeria -- Groundwater stability assessment with geospatial modeling using GIS: a case study of ILLIZI town, Algeria -- Efficiency assessment of AHP and fuzzy AHP in suitability mapping for artificial recharging (Case study: south of Kashan basin, Isfahan, Iran) -- Statistical methods for the evaluation of water quality -- Research on innovative materials and technologies for water treatment and water desalination: A conceptual analysis from 1969 to 2019 -- The Microbial and Physicochemical Analysis and Treatment of Groundwater of South Punjab, Pakistan -- Removal of cyanotoxins in drinking water using advanced oxidation processes -- Microplastic detection and analysis in water samples -- Column Adsorption Studies of phenolic compounds on nanoparticles synthesized from Moroccan phosphate rock -- Summary of Field Trial Results of the Treatment of Contaminated Water using Non-fouling Super Hydrophilic Functionalized Ceramic Membranes -- Preliminary study for phosphate recovery from starch factory wastewater using porous aluminum -- Removal of organic compounds from olive mill wastewater by flotation-anaerobic-aerobic processes and lime treatment -- Sustainable Wastewater Treatment Technologies for Appropriate Agricultural use in Jordan.
Keywords: Environmental management; Environmental engineering; Biotechnology; Bioremediation; Environmental monitoring; Water-power.; Renewable energy sources; Environmental chemistry; Environmental Management; Environmental Engineering/Biotechnology.; Environmental Monitoring; Hydroenergy; Renewable Energy; Environmental Chemistry